Decision-Making Processes in Illegal Abortions - Sh Shahbazi; N Fathizadeh; F Taleghani (JRI, 2008)
Introduction: Induced abortion is illegal in Iran and most other countries but in case pregnancy threatens maternal or fetal life, one can terminate the pregnancy, while doing illegal or clandes-tine and perhaps septic abortions usually leads to various undesirable life-threatening outcomes. The importance of exploring different aspects of illegal abortion and its related causes is an obvious subject. Therefore, this study investigates the experiences and views of some women and the outlook of authorities on illegal abortion practices. Materials & Methods: In this qualitative content analysis study, women that had a history of abortion and people with theological, political, legal or scientific (The patient care team) views were interviewed on illegal abortion outcomes in Karaj and Tehran, from March to September 2006. The data were content analyzed. Results: Five main themes emerged from this qualitative study. Only the results of one theme, “Assessment of condition”, with three main categories will be discussed in this article. These main categories included reactions, religious and personal beliefs and socio-political restrictions. The major reactions were divided into two minor subgroups 1) the treatment team, family and friends and the society. The medical team was further subdivided into two minor 2) supportive and preventive categories. The preventive subdivision 3) was divided into three minor divisions of abstaining from cooperation, caution and encouragement. Conclusion: Reactions of family and friends and the medical team to illegal abortions, are regarded as important for decision-making by pregnant women who want to commit them. False beliefs or incertitude in Sharia, and considering abortion of more benefit to the family compared to continuing it, all favor a state to ignore prohibitive ethical issues. The patient care team’s support also affects the way social restrictions are confronted and the pregnant women eventually commit abortion. Therefore, providing a separate consultation in health centers for women who have unwanted pregnancies could reduce abortion rates committed due to economic, social and family problems or being unaware of ethical and religious issues. Evaluation of the causes for assistance by the patient care team could help solve this health problem too.
Keywords: Illegal abortion, Content analysis, Patient care team, Religious beliefs, Personal beliefs, Family, Decision making, Reaction